(untitled) (Research, Society and Development, 2021)
Objectives: This study intends to present a protocol for a systematic review that seeks to compare hemodynamic changes in patients who underwent conscious oral sedation with diazepam versus midazolam during lower third molar extraction. Methods: Protocol for a systematic review of randomized clinical trials, using the databases Embase, PubMed/MEDLINE, Cochrane Library, Regional Portal of the VHL, gray literature and manual searches in the main journals in the field of maxillofacial surgery. This protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO), emphasizing that this review will be conducted in accordance with the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Final considerations: The need to maintain greater hemodynamic stability during lower third molar extraction, in the face of conscious oral sedation, makes it relevant that this systematic review be carried out.